Pengaruh Konten @Cahyanirynn Di Tiktok Terhadap Keputusan Pembelian Konsumen - Nur Lizamaulani; Abdul Latif Najmuddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2025)
Social media has become a key channel in digital marketing communication, with TikTok rapidly growing among young generations. This study aims to analyze the influence of TikTok influencer @cahyanirynn’s content on consumer purchase decisions of Artha body lotion. The study applies McQuail’s mass communication theory, new media concepts, and the AIDA model. A quantitative method was employed through a survey of 61 respondents selected using purposive sampling. Data were collected via questionnaires, observation, and documentation, then analyzed using simple linear regression. The findings reveal that TikTok content significantly influences consumer purchase decisions. In conclusion, influencer content on TikTok can attract attention, generate interest, create desire, and drive purchase decisions.